Discovery of an introduced Florida Flagfish (Jordanella floridae) population in Coastal Mississippi - Robert Ellwanger; Samuel E Hunt; Calvin R Rezac; Matthew D Wagner (Southeastern Fishes Council Proceedings, 2023)
The recent discovery of Jordanella floridae (Florida Flagfish) in Harrison County, Mississippi represents the first known occurrence of the species in the state. Native along the Atlantic and Gulf Coasts of Florida from Jacksonville to Tallahassee, this species has been introduced outside of its range via aquarium introductions. We hypothesize that an aquarium introduction was also the source of the newly discovered population, which has persisted at the location since 2020. Multiple collections of the species have been taken from a small waterbody which has a direct connection to the Tchoutacabouffa River (25mm-47mm TL). While it is unknown if this represents the only population in the system, further surveys should be conducted to determine population numbers at the site of collection, the extent of the invasion within the Tchoutacabouffa, and the impact to the native fish fauna.
Keywords: Aquarium transplant; native invasion; Cyprinodontidae